Five-Year Field Trial of Eight Camelina sativa Cultivars for Biomass to be Used in Biofuel under Irrigated Conditions in a Semi-Arid Climate - Richard H. Lohaus; Dhurba Neupane; Mitiku A. Mengistu; Juan K.Q. Solomon; John C. Cushman (Agronomy, 2020)
Camelina sativa is a promising oilseed crop used for dietary oil and as a biofuel feedstock. C. sativa is a highly adaptable, cool season crop that can be grown on marginal lands with minimal inputs, making it potentially suitable for growth in Northern Nevada and other cooler and drier semi-arid regions of North America. A five-year (2011 to 2015) field trial was conducted to evaluate the seed yield, oil content, and oil and biodiesel production potential of eight C. sativa cultivars in semi-arid regions of Northern Nevada. Columbia, Cheyenne, Calena, and Blaine Creek were ranked as the top four varieties based on the five-year study of mean seed yield, oil content, and estimated oil and biodiesel production values, although none of the cultivars were significant (p > 0.05). Overall, Columbia displayed the highest seed yield, harvest index, oil yield and potential biodiesel production of 910 kg ha−1, 0.147, 273.4 kg ha−1, and 86.4 L ha−1, respectively, across five growing seasons. For each individual year across the eight cultivars, seed yield, oil content, oil and potential biodiesel production was highest in 2015, and lowest in 2012 and 2013 (the drier years). The seed yields of this study fall within the ranges of yields reported in both the irrigated and rainfed locations of the Western United States. Based on the seed yield, oil, and the estimated oil and biodiesel productivity reported in this study, C. sativa can be grown successfully with supplemental irrigation in semi-arid environments like Nevada.